Nanomechanical Behavior of Top and Bond Layer in TBC - Cimenoglu, Huseyin; Akdemir, Müge; Canbolat, Merve; Bayram, Serra; Kılıc, Yasemın; Inceyer, Ahmet Arda; Aydin, Huseyin (My University, 2024)
Thermal barrier coatings (TBC) have been developed to reduce the surface temperature of hot components in gas turbine engines. To get superior oxidation and mechanical properties, “The Yttria Stabilized Zirconia (YSZ)” top coat and ?-NiAl bond coat are deposited by Electron Beam Physical Vapor Deposition (EB-PVD) and Chemical Vapor Deposition (CVD) processes, respectively. In this study, after structural characterization of the TBC formed on the directionally solidified (DS) CM247LC superalloy, the nanomechanical properties of the top and bond coats were determined using the nanoindentation technique. The results showed no significant differences in their elastic modulus despite the more than two times higher hardness of the top coat than the bond coat (18.4 GPa and 7.2 GPa, respectively). Energy Dispersive Spectrometry (EDS) equipped with Scanning Electron Microscope examinations revealed that Al and N- and N-rich zones within the bond coat have an underlying diffusion zone. In addition, thermal-grown oxide (TGO) film was detected at the interface of the top and bond coat.
Keywords: Microstructure; Thermal barrier coating; Aluminide coating; EB-PVD YSZ coating; Nanoindentation